Nanoscale Nonlinear PANDA Ring Resonator. - Yupapin, Preecha (CRC Press, 2012)
Microring/nanoring resonator is an interesting device that has been widely studied and investigated by researchers from a variety of specializations. This book begins with the basic background of linear and nonlinear ring resonators. A novel design of nano device known as a PANDA ring resonator is proposed. The use of the device in the form of a PANDA in applications such as nanoelectronics, measurement, communication, sensors, optical and quantum computing, drug delivery, hybrid transistor and a new concept of electron-hole pair is discussed in detail.